Pengaruh Terpaan Media Sosial terhadap Persepsi Risiko Kesehatan: Survei pada Isu Polusi Udara Jakarta - Abdurrohman, Yusuf; Sriharyani, Yuni; Syaiful, Muh.; Sembiring, Christa Dewi A. (Jurnal Studi Komunikasi dan Media, 2024)
The high level of air pollution in Jakarta had become a hot topic on various social media platforms in the second half of 2023. This research aims to find out whether and to what extent the level of exposure to social media influences the level of public health risk perception, especially regarding the problem of air pollution in Jakarta. The research was conducted only to Instagram, which is one of the most popular social media platforms in Indonesia. By using the concept of The Social Amplification of Risk Framework (SARF) to understand the role of media in shaping people's risk perceptions, this research uses quantitative approach with survey method on 109 respondents. The results of hypothesis testing show that exposure to information on Instagram related to Jakarta air pollution influences perception of health risk even though it is not the dominant factor. The results of this research show the need to utilize various communication channels to achieve more optimal results in risk communication. The use of omnichannel needs to be supported by an integrated communication strategy to provide message consistency and continuity so that people are able to understand risks correctly and adopt the right behavior to deal with them.